COULD WESTERN EXPERIENCE OF CAPITAL STRUCTURE MODEL APPLE TO DEVELOPING COUNTRIES: EVIDENCE ON CHINESE-LISTED COMPANIES - YAO, YIYING (2007)
ABSTRACT This paper examines the corporate financing behavior of the listed companies in the People's Republic of China. In this paper, it employs a Western experience of capital structure model, and applies the real data from Chinese firms. My results suggest that Western experience of capital structure model has the limited explanatory power in Chinese-listed companies. More specifically, some determinants of firm leverage ratio (i.e., profitability, firm size, grow opportunities and volatility) commonly cited in the studies on developed economies cannot apply to Chinese firms. In other words, these determinants generate opposite results when they apply to developed economies. Moreover, the Chinese evidence also suggests that listed firms tend to be a 'new Pecking order' when deciding the choice of financing. The significant difference mainly results from the different fundamental institutional, legal system, economy structure and ownership structure between Western countries and China.